2018
DOI: 10.1111/aos.13771
|View full text |Cite
|
Sign up to set email alerts
|

A noninterventional study to monitor patients with diabetic macular oedema starting treatment with ranibizumab (POLARIS)

Abstract: POLARIS showed that real-world outcomes in DME patients starting treatment with ranibizumab were lower than those observed in clinical studies, in spite of extensive monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
3
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 29 publications
4
16
3
3
Order By: Relevance
“…These numbers are also consistent with those reported for aflibercept in randomized controlled trials [22]. In routine clinical practice, the number of anti-VEGF injections is likely to be lower than the licensed posology, as shown in the POLARIS study [7], where the mean number of injections in year 1 was 4.9; however, outcomes in that study were suboptimal in comparison with other randomised controlled trials. Injection numbers were modeled to decrease [21] in years 2 and 3 to account for treat-and-extend dosing regimens [23].…”
Section: Scenario 1 (Current Pathway): Continued Treatment With Aflibsupporting
confidence: 82%
See 1 more Smart Citation
“…These numbers are also consistent with those reported for aflibercept in randomized controlled trials [22]. In routine clinical practice, the number of anti-VEGF injections is likely to be lower than the licensed posology, as shown in the POLARIS study [7], where the mean number of injections in year 1 was 4.9; however, outcomes in that study were suboptimal in comparison with other randomised controlled trials. Injection numbers were modeled to decrease [21] in years 2 and 3 to account for treat-and-extend dosing regimens [23].…”
Section: Scenario 1 (Current Pathway): Continued Treatment With Aflibsupporting
confidence: 82%
“…Anti-VEGF drugs and steroid implants have superseded thermal laser treatment as the mainstay of treatment for DME over the past decade due to the ability of these agents to stabilize and even achieve a subjective improvement in vision [6,7]. Recent studies, however, have indicated poor visual outcomes in one-third of patients after 2 years of continued anti-VEGF treatment, which may be due to a combination of factors, including a suboptimal response to the drug administered (i.e., visual and anatomic parameters indicating that a patient is not benefiting from continued treatment), suboptimal drug delivery (i.e., inadequate delivery of the drug to the eye), and poor compliance [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Several real-world studies on ranibizumab in DME have evaluated treatment patterns and outcomes over periods of 9 to 24 months. [22][23][24][25][26][27][28][29][30][31][32][33][34][35] Mean number of ranibizumab injections ranged from 3.1 to 7.2. VA gains varied between +0.0 and +8.4 letters with CRT reductions ranging from −83.9 µm to −164.6 µm.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important to evaluate the efficacy of ranibizumab therapy in a real-world clinical setting, where not all patients receive the initial monthly injections and follow-up visits are missed. Furthermore, differences in health systems, resource availability, patient characteristics, and local practice exist among countries, as reported by several recent studies [ 17 19 ]. We were aiming to evaluate the outcomes achieved in the largest ophthalmology clinic in Lithuania.…”
Section: Discussionmentioning
confidence: 99%
“…Other real-world studies also reported low numbers of ranibizumab injections. There was an average of 3 to 6 injections over the first year in studies which did not exclude eyes based on the number of injections [ 17 19 , 21 ].…”
Section: Discussionmentioning
confidence: 99%